Characterisation of Nano-Calcium Lactate from Chicken Eggshells Synthesized by Precipitation Method as Food Supplement - Agus Hadi Prayitno; T A Siswoyo; Y Erwanto; T Lindrianti; Sri Hartatik; Joni Murti Mulyo Aji; Edi Suryanto; Rusman Rusman (Indonesian Center for Animal Research and Development (ICARD), 2021)
Osteoporosis can be prevented by consuming calcium lactate. Calcium that is consumed is generally in a micro-size. Micro-sized calcium is only absorbed by the body by about 50% which can cause deficiency. Eggshells are poultry waste that is rich in calcium and can be used as a cheap source of dietary calcium through nanotechnology. Nanotechnology has been developed to increase calcium absorption. This study aimed to synthesize nano-calcium lactate from chicken eggshells,and commercial calcium oxide by precipitation method. Synthesis was carried out by reacting a solution of 1 mol/L eggshell calcium oxide and commercial calcium oxide (control) as much as 20 ml mixed with a solution of 6 mol/L lactic acids as much as 30 ml with a ratio of 1:1.5 (v/v) for 30 minutes at 50°C at a speed of 500 rpm/minute using a magnetic stirrer. Ethanol 50% was added as much as 20 ml (v/v), oven-dried at 105°C for 72 hours then crushed to produce eggshell nano-calcium lactate (NCaL) powder. Characterisation of NCaL using Transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR). Result showed that NCaL in the form of white crystals could be synthesized from chicken eggshells by precipitation method. Characterization with XRD showed that the diffraction angle was 2θ with the peaks of NCaL, namely 9.3800°, 10.3869°, and 22.9570°. Characterization with FTIR obtained a peak in the wavenumber from NCaL, namely 1,589.34 cm-1. Characterization using TEM showed that the crystal size of NCaL was 75 nm.